A survey on existing challenges of BSC implementation for performance measurement - Behdad Gitinejad; Mohammad Ali Keramati (Management Science Letters)
The balanced scorecard (BSC) is a strategic oriented tool used comprehensively in profit and nonprofit organizations all over the world to synchronize routine processes of organizations to the mission and strategy, improve inner and outter communications, control organization performance toward strategic targets. BSC has emerged from a simple performance measurement framework to a comprehensive strategic management system. It changes an organization’s strategic plan from a passive document to an active guideline for the organization on a daily basis and provides a helpful assistance that not only enables performance measurements, but also helps planners identify what should be accomplished and measured. This study focuses on how BSC is adopted as a tool for measuring effectiveness of strategy implementation in these organizations. This study adapts the BSC as a powerful tool for reaching an organization’s performance in four significant areas: Financial perspective, Customer-Market perspective, Internal Processes perspective and Learning & Growth perspective. The results suggest that governmental organizations are somehow successful in achieving their objectives in various degrees.